2003
DOI: 10.1088/0034-4885/66/3/203
|View full text |Cite
|
Sign up to set email alerts
|

Simulated dynamics and biological macromolecules

Abstract: We present a review of the use of molecular dynamics techniques to study the behaviour of proteins. The application of such methods to biological macromolecules has evolved directly from its use to study simpler physical and chemical systems. We describe the methods typically used in producing multiple nanosecond atomic trajectories. This technique is now so common that it is impossible to review the whole area. Therefore, we have focused on three areas, namely the application to proteins of biomedical importa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
32
0

Year Published

2004
2004
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 127 publications
0
32
0
Order By: Relevance
“…Such simulations have been successfully applied, for example, to enzyme reactions, protein folding, ion channels, and membrane fusion. [24][25][26][27][28][29][30][31] Computer simulation studies for the interaction between carbon nanoparticles and biological materials such as proteins and DNA have also been performed. [32][33][34][35][36][37][38] The inhibition of the HIV-1 protease by fullerenes and their derivatives 32,[36][37] was studied and the binding behavior of carbon nanotubes with nucleic acids 34,38 or amylose 33 was also investigated to improve the solubility of nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…Such simulations have been successfully applied, for example, to enzyme reactions, protein folding, ion channels, and membrane fusion. [24][25][26][27][28][29][30][31] Computer simulation studies for the interaction between carbon nanoparticles and biological materials such as proteins and DNA have also been performed. [32][33][34][35][36][37][38] The inhibition of the HIV-1 protease by fullerenes and their derivatives 32,[36][37] was studied and the binding behavior of carbon nanotubes with nucleic acids 34,38 or amylose 33 was also investigated to improve the solubility of nanotubes.…”
Section: Introductionmentioning
confidence: 99%
“…Advances in molecular dynamics [19,20] and Monte-Carlo [21] simulations have resulted in the enhanced sampling of phase space for complex biological systems [22][23][24][25][26][27][28]. Several methods attempt to probe more of the molecule's conformational space, such as the extension of the simulation to longer time periods [17,[29][30][31][32], guided enhanced sampling [33], multiple short-time trajectories [11,[34][35][36][37][38], simulated annealing [39], conformational flooding [40,41], and locally enhanced sampling [42][43][44].…”
Section: Introductionmentioning
confidence: 99%
“…Several methods attempt to probe more of the molecule's conformational space, such as the extension of the simulation to longer time periods [17,[29][30][31][32], guided enhanced sampling [33], multiple short-time trajectories [11,[34][35][36][37][38], simulated annealing [39], conformational flooding [40,41], and locally enhanced sampling [42][43][44]. In this study, we review the simulation work of multiple trajectories previously reported, [34] since recent studies indicate that this approach improves the sampling of conformational space; [11,23,[34][35][36]40,[45][46][47][48] however, a more quantitative assessment of the actual time extension has not been presented.…”
Section: Introductionmentioning
confidence: 99%
“…One of the best established methods for generating an ensemble from a known static structure is MD, reviewed in Ref. 17. The ensemble generated by this technique is like a movie, in that frames have a well defined temporal relationship with each other.…”
mentioning
confidence: 99%